Hopf Bifurcation Analysis of a Predator-Prey Biological Economic System with Nonselective Harvesting - Biwen Li; Zhenwei Li; Boshan Chen; Gan Wang (Discrete Dynamics in Nature and Society)
A modified predator-prey biological economic system with nonselective harvesting is investigated. An important mathematical feature of the system is that the economic profit on the predator-prey system is investigated from an economic perspective. By using the local parameterization method and Hopf bifurcation theorem, we analyze the Hopf bifurcation of the proposed system. In addition, the modified model enriches the database for the predator-prey biological economic system. Finally, numerical simulations illustrate the effectiveness of our results.